Systematic literature review: The effect of technology utilization and internal supervision on the quality of financial reports - Tari Apriani; Sri Rahayu; Wirmie Eka Putra (ARKA INSTITUTE, 2026)
This study seeks to examine the impact of technology use and internal oversight on the quality of financial reports through a Systematic Literature Review (SLR) methodology. The study gathered 30 pertinent journal papers published from 2020 to 2025 via Google Scholar. The data were subjected to thematic analysis to discern patterns, correlations, and discrepancies in prior findings. The findings demonstrate that the deployment of information technology, encompassing accounting information systems like AIS and governmental applications, typically enhances the accuracy, timeliness, and reliability of financial reporting. Nonetheless, numerous studies indicate variable results, implying that the efficacy of technology is contingent upon the quality of execution, user proficiency, infrastructure preparedness, and organizational backing. Internal supervision, encompassing internal audit and control systems, regularly demonstrates a substantial and favorable effect on the quality of financial reports by improving transparency, compliance, and error mitigation. The amalgamation of efficient technology and robust internal oversight yields superior outcomes. This study underscores the significance of governance, human resources, and system preparedness in attaining superior financial reporting, particularly within the public sector framework.